The Influence of Service Quality and Tariff on the Passenger Share of Indonesian Airlines (Low-Cost Carrier Aviation) - Yhani Mardani, Ratih Hurriyati, Disman, Vanessa Gaffar (International Journal of Advanced Science and Technology, 2020)
The low level of customer loyalty to the mode of air transportation services in Indonesia is due to competitive conditions that make it very difficult for customers to determine which airlines are superior compared to other airlines. This has an impact on passenger shares. This condition also relates to problems in service quality and tariffs imposed. So based on this background, this study aims to examine the influence of service quality and tariff on passenger share of the Indonesian airlines (Low Cost Carrier Aviation). This study employs quantitative approach. The unit of analysis of this study is low cost carrier aviation. The observation unit is low cost carrier aviation passengers in Indonesia. Observations in this study using the time horizon is cross section / one shoot, which is in 2019. The study used the primary data obtained from the questionnaire of 100 passengers from the airline. To test the hypothesis, the partial least squares PLS is used. The results show that service quality and tariff have a significant effect on passenger share. Service quality has a more dominant influence than tariff in increasing passenger share. The results of this study have implications for the management of Indonesian Airlines (Low Cost Carrier Aviation) that service quality is an aspect that needs to be prioritized in an effort to increase customer share, especially by developing reliability aspects, and by improving suitability in tariff setting.